Sustainability and the historical trajectory of environmental movements - Manca, Ricardo da Silva; Schiavon, Isabel Cristina Adão; Sebastiani, Rafael Teixeira; Passos, Christian Ricardo Silva; Marques, Francisco Roldineli Varela; Nascimento, Glauber Gonçalves do; Filho, Teodoro Antunes Gomes; Silva, Manoel Messias da; Sousa, Weverton Wylar Silva de; Caldeira, Fernanda Marques; Nogueira , Carla Rossana de Araújo Torres (Seven Editora, 2024)
The present research aimed to analyze the evolution of sustainable awareness over time, focusing on the main historical milestones, initiatives and practices adopted, as well as the results achieved so far. To carry out this study, the methodology of bibliographic research was used through a survey of data in articles, theses, dissertations and books. As a result, it was found that sustainable awareness has been an increasingly relevant topic over the years, driving initiatives and practices aimed at preserving the environment and promoting sustainable development. In addition, it was possible to observe that the theme has been addressed by various sectors of society, such as business, government, and education, demonstrating the importance of sustainable awareness for the construction of a fairer and more balanced future for the next generations. DOI:https://doi.org/10.56238/sevened2023.001-021